Effect of electrospraying conditions on the properties of aspalathin‐Eudragit S100 nanoparticles and assessment of orogastrointestinal stability and membrane permeability. Issue 2 (18th January 2022) - Human, Chantelle; De Beer, Dalene; Bowles, Sandra; Joubert, Elizabeth
Abstract: Aspalathin, a C ‐glucosyl dihydrochalcone, could have beneficial effects in the gut through the modulation of the microbiome. However, aspalathin is susceptible to oxidative degradation. The effect of electrospraying conditions on encapsulation of an aspalathin‐rich fraction prepared from green rooibos (GRAF; 40% aspalathin, m/m) with Eudragit S100 (ES100), a pH‐sensitive release polymer, was investigated to enhance the stability of aspalathin. Electrospraying conditions were varied according to a central composite design, using ES100 concentrations of 1–6% (m/m), GRAF concentrations of 5–25% (m/m, relative to polymer concentration), and voltages of 10–25 kV. The varying conditions produced nanoparticles ranging in yield (60.3–83.7%), encapsulation efficiency, (20.5–81.8%), loading capacity (1.0–14.9%), particle size (183–260 nm), and polydispersity index (0.35–0.74). The GRAF nanoparticles and nanoparticles prepared with pure aspalathin were evaluated for stability and release of aspalathin at fixed pH–time combinations (pH 6.8, 5 min; pH 2, 120 min; pH 4, 60 min; and pH 7, 120 min), simulating the pH and residence/transit time at various locations of the orogastrointestinal tract. Nanoencapsulation decreased aspalathin degradation at all pH‐time combinations (1.9–2.7 times less degradation; p  < 0.05), except for pH 7, 120 min ( p ≥ 0.05), thus offering protection from the pH of the upper gastrointestinal tract. Additionally, the parallel artificial membrane permeability assay and the Caco‐2 monolayer model indicated that the low membrane permeability of aspalathin after nanoencapsulation was maintained that would limit absorption, ideal for delivery in the gut. Thus, nanoencapsulated aspalathin holds potential for the regulation of gut microbiota. Abstract : The effect of electrospraying conditions on encapsulation of an aspalathin‐rich fraction prepared from green rooibos with Eudragit S100 (ES100) was investigated. The stability and permeability of resultant nanoparticles were investigated in terms of suitability as a colon‐targeted delivery system for aspalathin.